2007
DOI: 10.1080/15563650601072191
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of gestational exposure to alprazolam by analysis of biological matrices in a newborn with neonatal sepsis

Abstract: The newborn of a mother reporting alprazolam use during pregnancy presented with respiratory distress and clinical features consistent with neonatal withdrawal syndrome or neonatal sepsis of vertical transmission. Alprazolam and its main metabolite (alpha-hydroxyalprazolam) were detected in cord serum, neonatal urine and also in neonatal hair, meconium and placenta, accounting for both acute and chronic exposure to this benzodiazepine during intrauterine life. At the same time, the clinical diagnosis of neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Alprazolam and its metabolite α-hydroxyalprazolam were detected in meconium and placenta in nearly the same concentrations (7–9 ng/g) in a mother who reported consumption of 1.5-mg/day alprazolam during pregnancy 32. In another case, a mother drinking 1L/day of homemade mate containing 930 mg caffeine and 620 mg theobromine had higher placenta (caffeine 56.9 ng/g, theobromine 45.3 ng/g) than meconium concentrations (caffeine 27.0 ng/g, theobromine 40.1 ng/g) 33.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Alprazolam and its metabolite α-hydroxyalprazolam were detected in meconium and placenta in nearly the same concentrations (7–9 ng/g) in a mother who reported consumption of 1.5-mg/day alprazolam during pregnancy 32. In another case, a mother drinking 1L/day of homemade mate containing 930 mg caffeine and 620 mg theobromine had higher placenta (caffeine 56.9 ng/g, theobromine 45.3 ng/g) than meconium concentrations (caffeine 27.0 ng/g, theobromine 40.1 ng/g) 33.…”
Section: Discussionmentioning
confidence: 86%
“…Few published placenta drug data following in utero exposure are available 3235, with only 3 studies also reporting meconium results 3234. Alprazolam and its metabolite α-hydroxyalprazolam were detected in meconium and placenta in nearly the same concentrations (7–9 ng/g) in a mother who reported consumption of 1.5-mg/day alprazolam during pregnancy 32.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, similar concentrations of arecoline (the main alkaloid of the areca nut) were found in placenta and meconium; arecoline was detected in placenta and showed a range concentration of 9-14 ng/g of tissue and the respective meconium specimens showed a range between 8 and 17 ng/g [11]. Garcia-Algar et al reported the detection of similar concentrations of alprazolam and a-hydroxyalprazolam in placenta and meconium after alprazolam doses of 1.5 mg/day [12]. In addition, Martin et al described neonatal withdrawal syndrome after maternal consumption of mate during pregnancy, and reported the presence of caffeine and theobromine in placenta and other neonatal matrices [13].…”
Section: Introductionmentioning
confidence: 82%
“…Martin et al (43) described NAS after maternal consumption of mate (traditional infusion from subtropical South America prepared by steeping yerba mate, Ilex paraguariensis , in hot water) and reported the presence of caffeine and theobromine in placenta among other maternal and neonatal matrices. Garcia-Algar et al (44) reported detection of similar concentrations of alprazolam and α-hydroxyalprazolam in placenta and meconium after alprazolam doses two or three times those normally prescribed (1.5 mg/day). Also, similar concentrations of arecoline (main alkaloid of the areca nut) were found in placenta and meconium from six newborns exposed to this compound throughout pregnancy; arecoline was detected in five out of six placentas (9–14 ng/g) and in four meconium specimens (8–17 ng/g) (45).…”
Section: Discussionmentioning
confidence: 99%